Distribution and Polarization of Hematogenous Macrophages Associated with the Progression of Intervertebral Disc Degeneration. Issue 4 (15th February 2022) - Yamamoto, Yusuke; Kokubo, Yasuo; Nakajima, Hideaki; Honjoh, Kazuya; Watanabe, Shuji; Matsumine, Akihiko
Abstract : In the disc puncture model, bone marrow-derived macrophages increased in the endplates of vertebral discs with progression of disc degeneration, and their polarity was M2-dominant. This observation might lead to development of a novel therapeutic target for the prevention of intervertebral disc degeneration. Abstract : Study Design: In vivo study using immunostaining and immunoblot analysis. Objective: To determine the distribution of bone marrow-derived macrophages (BMDMs), macrophage polarization and cytokine expression in the process of intervertebral disc (IVD) degeneration. Summary of Background Data: Knowledge of the detailed distribution of exogeneous macrophages in the disc degeneration process is important for understanding the pathomechanisms and establishing novel therapeutic targets. Methods: To distinguish BMDMs, GFP-labeled bone marrow chimeric rats (n = 12) were generated. The degenerative process of the intervertebral disc was reproduced in a rat caudal disc puncture model (n = 49). Immunofluorescence staining was performed to observe the distribution of BMDMs, Iba-1 and GFP double-positive cells, and Iba-1 and iNOS (M1 macrophage) or arginase-1 (M2 macrophage) double-positive cells. Immunoblot analysis was used to evaluate differences in cytokines (TNF-α, IL-1β, IL-6, TGF-β, IL-4, and IL-10) depending on the distribution of BMDMs. Results: BMDMs infiltrated into the outer annulus fibrosus and endplate, while increasing tissue-resident macrophage was observed inside the annulus fibrosus/nucleus pulposus. The ratio of BMDMs and the polarity change differed among the regions. Especially in the endplate, BMDMs increased gradually and the macrophage phenotype was M2 dominant. Expression of IL-1β decreased gradually at endplate, and that of IL-4 increased early after disc puncture at inside of the annulus fibrosus. Conclusion: During the disc degeneration process, BMDMs were observed mainly around the endplate and outside area of the annulus fibrosus, with few in the inside area of annulus fibrosus and nucleus pulposus. Compared to other IVD area, macrophage polarity and cytokine expression is concomitantly M2-dominant in endplate. Increased hematogenous M2-phenotype macrophages in endplate with progression of IVD degeneration could enhance our understanding of the underlying mechanisms of disc degeneration. Level of Evidence: N/A